(untitled) (Revista de Ciências Agroveterinárias, 2020)
The soil persistence of herbicides from the triazines group is basically dependent on precipitation conditions and soil characteristics. The objective of this study was to assess the residual effect of different application times and atrazine and atrazine + simazine doses for the soybean crop. Experiments were conducted in the field and greenhouse. In the field, the design of subdivided plots with four replications was used, with factor A composed of application times 56, 49, 42, 35, 28, 21, and 14 days before soybean sowing; and factor B, by the herbicides atrazine and atrazine + simazine. For the greenhouse experiment, the design was completely randomized blocks, factor A doses 0, 570, 1140, 1715, 2285, 2860, 3430, and 4000 g i.a. ha-1, factor B herbicides atrazine and atrazine + simazine. The application of the treatments was carried out with a CO2 pressurized sprayer, after the application of the soybean. The field was assessed regarding the plant stand, phytotoxicity, stature, height of insertion of the first training, chlorophyll content, and kg ha-1 yield. In the greenhouse, phytotoxicity, plant height, leaf area, and dry mass were assessed. Then, data were submitted to analysis of variance and, when significant, the means were compared by the Tukey test at 5%. The residual simulation of the herbicides atrazine and atrazine + simazine in the soil showed similar behavior regarding the effects on soybean. In the field experiment, due to the high precipitations that occurred in the interval between herbicide applications and soybean sowing, no phytotoxic effects or reduction in crop yield were observed. In the greenhouse, increasing the residual dose of herbicides in the soil increased the toxic effects on soybean.